EFFECT OF THINK-PAIR-SHARE STRATEGY ON ACHIEVEMENT IN MATHEMATICS IN RELATION TO MATHEMATICAL CREATIVITY (International Journal of Food and Nutritional Sciences, 2022)
The present study investigates the effect of think-pair-share on achievement in mathematics in relation to mathematical creativity. The sample consisted 84 students of class 6th selected from three different schools of Amritsar (Punjab). Instructional material based on think-pair-share was prepared and utilized to teach the experimental group. The tools was used for data collection were on achievement in mathematics developed by the investigator and mathematical creativity developed by Sharma and Sansanwal (2012) was also administered. After pre- testing and posttesting on all the students, gain scores were computed. The mathematical creativity test was also administered. Mean, SD, Analysis of Variance (2×3) and t- ratio were used to arrive at the conclusions – (i)The achievement in mathematics of high mathematical creativity experimental group was found significantly higher as compared to the control group. (ii) The achievement in mathematics of average mathematical creativity experimental group was found significantly higher as compared to the control group. (iii) The achievement in mathematics of low mathematical creativity experimental group was found significantly higher as compared to the control group. (iv) No significant interaction effect was found between the two variables.